Health profile of the population that attended to an integral health campaign in the time of covid-19 at a peruvian city: Perfil epidemiologico de la poblacion que acude a una campaña de salud integral en tiempo de covid-19 en una ciudad peruana - Huaraca-De los Santos, Edgar M. (2022)
Objective: The aim of the study was to determine the health profile of the population that attended an integrated health campaign in times of COVID-19.  Materials and Methods: It was a Cross-sectional, observational, descriptive, and retrospective study. The population is made up of a total of 289 patients who met the selection criteria.  Results: Of the total number of patients (289), 64.7% were female, from this group 8.3% reported having had COVID-19. COVID-19 cases were reported to be between the ages of 15 to 59 years (37%). The most frequent comorbidity was: obesity (26.6%), followed by arterial hypertension (11.8%) and diabetes mellitus (3.8%). The most frequent signs and symptoms of COVID-19 were: dyspnea (4.5%), myalgia (4.2%), cough (3.1%), and rhinorrhea (3.1%). Only 19.7% of patients reported having received the COVID-19 vaccine at the time of the study. The most frequently reported pathologies were: respiratory (26.3%), musculoskeletal (25.3%), endocrinological (12.1%), cardiovascular (11.1%), and infectious pathologies (11.1%). The associated variables were: no comorbidity (p = 0.014; CI 95 [0.208-0.853]; OR = 0.421), obesity (p = 0.010; CI 95% [1.228-5.161] OR = 2.518), and dyspnea (p = 0.000; CI 95 [4,052-22,980], OR = 9,649).  Conclusions: A predominance of female patients was found. Obesity was the most frequent comorbidity. The most frequent pathologies were those of the respiratory system. The absence of comorbidities shows a protective association for COVID-19, while obesity and dyspnea increase this association.